Changes in odorants and flavor profile of heat‐processed beef flavor during storage. Issue 12 (9th November 2022) - Zhang, Zeyu; Blank, Imre; Wang, Bei; Cao, Yanping
Abstract : Abstract: Flavor quality changes of heat‐processed beef flavor (HPBF) upon storage are greatly affected by storage conditions. Flavor characterization of HPBF stored for 168 days resulted in 17 key odor‐active compounds having flavor dilution factors log3 FD ≥ 3 and odor activity values > 1. Based on the concentration changes of these key odorants, a total of 13 HPBF samples were divided into four groups by hierarchical cluster analysis. Combined with flavor profile analysis, the overall flavor of HPBF gradually changed from a characteristic beef aroma to burnt and fermented soybean paste‐like notes. Some of the 17 key odorants, such as 2‐methyl‐3‐furanthiol, 2‐furfurylthiol, methyl furfuryl disulfide, and difurfuryl disulfide, contributed to the characteristic beef aroma of the freshly prepared product and in the early stage of storage. On the other hand, the odor‐active compounds 2‐methylbutanal, dimethyl disulfide, dimethyl trisulfide, and 2‐ethyl‐3, 5‐dimethylpyrazine were associated with the later stage of storage showing a positive correlation with the intensity of burnt and fermented soybean paste‐like notes. A molecular understanding of flavor profile changes of HPBF during storage will provide the basis for developing characteristic beef aroma notes and maintaining the keeping quality of beef products upon storage. Practical Application: The relationship between sensory quality and changes in odorant concentration of heat‐processed beef flavor during storage will provide the molecular basis for developing high‐quality thermal reaction meat flavorings.